2017
DOI: 10.1021/acs.jpcb.6b11540
|View full text |Cite
|
Sign up to set email alerts
|

Ion-Specific Modulation of Interfacial Interaction Potentials between Solid Substrates and Cell-Sized Particles Mediated via Zwitterionic, Super-Hydrophilic Poly(sulfobetaine) Brushes

Abstract: Zwitterionic polymer brushes draw increasing attention not only because of their superhydrophilic, self-cleaning capability but also due to their excellent antifouling capacity. We investigated the ion-specific modulation of the interfacial interaction potential via densely packed, uniform poly(sulfobetaine) brushes. The vertical Brownian motion of a cell-sized latex particle was monitored by microinterferometry, yielding the effective interfacial interaction potentials V(Δh) and the autocorrelation function o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 37 publications
(64 reference statements)
2
19
0
Order By: Relevance
“…71−73 However, timeresolved in situ NR measurements, using the time-of-flight method with a powerful wide-wavelength band pulsed neutron beam, are valid for the tracking of structure evolution of soft interfaces in response to the environment. 74,75 Some timeresolved NR measurements have already been applied for the investigation of the structure evolution process of polymer films. 74,76 We foresee that the insights obtained by our research are valuable in the design of materials covered with polyzwitterion brushes tailored to medical products.…”
Section: ■ Conclusion and Perspectivementioning
confidence: 99%
“…71−73 However, timeresolved in situ NR measurements, using the time-of-flight method with a powerful wide-wavelength band pulsed neutron beam, are valid for the tracking of structure evolution of soft interfaces in response to the environment. 74,75 Some timeresolved NR measurements have already been applied for the investigation of the structure evolution process of polymer films. 74,76 We foresee that the insights obtained by our research are valuable in the design of materials covered with polyzwitterion brushes tailored to medical products.…”
Section: ■ Conclusion and Perspectivementioning
confidence: 99%
“…Polyzwitterionic brushes contain both positive and negative charges, and as with polyanionic or polycationic brushes, the strong affinity of these charged groups for water leads to superhydrophilic films that are attractive as antifouling coatings. Nevertheless, the strong inter- and intramolecular associations between opposite charges in polyzwitterionic brushes lead to unusual trends in swelling. For example, in contrast to polyanionic or polycationic films, poly­(sulfobetaine methacrylate) (PSBMA) brushes show enhanced swelling in aqueous solutions with increasing ionic strength. …”
Section: Introductionmentioning
confidence: 99%
“…As described the previous section, it is still challanging to deal with ion specific interactions of charged polymers. For example, Wang et al reported the anion-specific changes in conformation and protein repellency for poly-sulfobetaine follow Hofmeister series (Wang et al, 2013), while Higaki et al suggested that the dependence of effective interaction potentials on cations cannot be explained by this framework (Higaki et al, 2017). It also seems plausible that the conformational fluctuation of molecules entropically repells proteins and cells from the surface.…”
Section: Toward Rational Design Of New Materials: Bioinertnessmentioning
confidence: 99%